Quinolone resistance phenotype and genetic characterization of Salmonella enterica serovar Pullorum isolates in China, during 2011 to 2016 - Xiaodong Guo; Honglin Wang; Yiluo Cheng; Wenting Zhang; Qingping Luo; Guoyuan Wen; Guijun Wang; Huabin Shao; Tengfei Zhang (BMC Microbiology, 2018)
Abstract Background Pullorum disease, caused by Salmonella enterica serovar Pullorum (S. Pullorum), is one of the most important bacterial infections in the poultry industry in developing countries, including China. To examine the prevalence and characteristics of S. Pullorum, the Multilocus Sequence Typing (MLST) genotypes, fluoroquinolones resistance, and biofilm-forming abilities of S. Pullorum isolates were investigated, collected from 2011 to 2016 in China. Results Thirty S. Pullorum isolates collected from 2011 to 2016 were analyzed. Quinolones susceptibility testing showed that 90% of the isolates were resistant to the first generation of quinolines nalidixic acid, but the resistance rates to different fluoroquinolones agents were lower than 13.3%; for some there was even no resistance. Multilocus sequence typing (MLST) showed that ST-92 was the dominating genotype, accounting for 90.0% of all S. pullorum strains. The remaining three isolates were of the new reported sequence type ST-2151. Interestingly, the Asp87Gly substitution in quinolone resistance-determining regions (QRDR) of GyrA was only observed in the three strains of ST-2151, suggesting a potential correlation between Asp87Gly substitution and sequence type (p < 0.05). However, Asp87Gly substitution could not confer the resistant to ofloxacin and ciprofloxacin of these isolates. The plasmid-mediated quinolone resistance (PMQR) gene was not found in any of the tested isolates. Furthermore, an assay measuring biofilm-forming abilities showed that 46.7% of the isolates were non-biofilm producers, while 53.3% could form very weak biofilms, which might explain the relatively lower resistance to fluoroquinolones. Conclusions We reported a high resistance rate to the first generation of quinolines nalidixic acid and relatively low resistance rates to fluoroquinolones in S. Pullorum isolates. In addition, weak biofilm-forming abilities were found, which might be an important reason of the low fluoroquinolones resistance rates of S. Pullorum isolates. ST-92 was the dominating genotype demonstrated by MLST, and the new sequence type ST-2151 showed a potential correlation with Asp87Gly substitution in QRDR of GyrA. We believe the characterization of these S. Pullorum isolates will be helpful to develop prevention and control strategies.